Effect of Carbon Dioxide Concentration on the Growth Response of Chlorella vulgaris Under Four Different Led Illumination - Rendon, Sebastian Mejia; Roldan, Gabriel Jaime Colmenares; Voroney, R. Paul (International Journal of Biotechnology for Wellness Industries, 2013)
This experiment examined the growth response of Chlorella vulgaris exposed to CO2 concentrations increasing from ambient to 8.5% and under white, blue, red and red-blue lights after 15 days incubation. Biomass production increased with increasing CO2 concentrations under all light sources. The highest biomass production, 1.59 g L-1, was obtained when the algae were supplied with 8.5% CO2 and exposed to white light. Biomass production under blue, red and red+blue light was 1.53 g L-1, 0.45 g L-1 and 1.27 g L-1, respectively. The research suggests that C. vulgaris is not able to adapt production of its photosynthetic pigments to absorb light sources different that it is normally has evolved to.